Metabolism of estradiol fatty acid esters in man - Hershcopf, R J; Bradlow, H L; Fishman, J; Swaneck, G E; Larner, J M; Hochberg, R B (The journal of clinical endocrinology and metabolism, 1985)
Fatty acid esters of estradiol coupled at the C-17 position are naturally occurring metabolites of estradiol (E2). They have been recovered after incubation of E2 with human tissue and identified in human plasma. We investigated the primary metabolic transformation of E2, namely C-17 oxidation, of two representative fatty acid esters, in five normal subjects (four men and one woman), aged 25-55 yr, using a radiometric method. The transfer of tritium from the C-17 alpha position to tritium water after iv injection of free E2 was compared to that of E2-17 beta-stearate and E2-17 beta-arachidonate. Both esters were oxidized at the C-17 position to a greater extent than was free E2. In addition, the oxidation of the E2 fatty acid esters proceeded more slowly. Thus, the time necessary to reach half the maximal extent of reaction ranged from 30-45 min for the three E2-17 beta-arachidonate studies and from 2.5-4 h for the five E2-17 beta-stearate studies, while that for free E2 was less than 15 min in each instance. The disappearance of intact E2-17 beta-stearate from plasma after bolus injection was studied in two subjects (one of the five above and one additional subject). The t1/2 values calculated for the 0-60 min period were 24 and 16 min. The rate of disappearance E2-17 beta-stearate was slower than that of E2. The biological activity of E2 esters is thought to reside in their ability to be converted, by hydrolysis, to free E2. The E2 esters must undergo hydrolysis before the oxidation of free E2 to estrone can proceed. Since the oxidation reaction is extremely rapid, studying the rate of oxidation after injection of the E2 fatty acid esters provides an index of their in vivo hydrolysis and, thus, a measure of their subsequent biological activity as the free hormone. The unsaturated arachidonate ester of E2 was oxidized at a faster rate than the saturated stearate ester; this implies that the hydrolysis of the arachidonate ester was faster. Evidence of continuing oxidation of E2-17 beta-stearate at times well after its level in plasma markedly decreased indicates that the ester is removed from the circulation before its subsequent hydrolysis and oxidation. We conclude that in man, the C-17 oxidation of both E2-17 beta-arachidonate and E2-17 beta-stearate proceeds more slowly but to a greater extent than that of the free steroid.